La logica dell'evoluzione dei viventi : spunti di riflessione. Atti del XII convegno del gruppo italiano di biologia evoluzionistica: Firenze, 18-21 febbraio 2004 - Scapini, Felicita (Atti, 2005)
The book collects the works presented during the XII meeting of the Italian Group of Evolutionary Biology, held in Florence in February 2004. Evolutionary theories are illustrated with balance from different points of view (from the perspective of historians, zoologists, paleontologists, anthropologists, molecular biologists) in the light of some recent experimental and theoretical discoveries. The debate and the diversity of investigations demonstrate the validity and relevance of the study of biological evolution.